2021
DOI: 10.1016/j.jen.2021.03.013
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Analysis of the Impact of the Coronavirus Disease 2019 Pandemic on Health Care Workers in a Tertiary Hospital in Turkey

Abstract: Background Several vaccines have been developed and approved for use against SARS-CoV-2; however, the use of personal protective equipment (PPE) and precautions against transmission remain important due to the lack of effective specific treatment and whole community immunity. Hydroxychloroquine sulfate (HCQ) was used as a treatment option in the early days of the pandemic; however, it was subsequently removed due to a lack of evidence as an effective treatment for COVID-19. Aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
1
0
0
Order By: Relevance
“…Since HCQ has proven to be able to prevent SARS-CoV-2 infection in vitro,31 32 a number of clinical trials and observational studies embarked on evaluating HCQ as prophylaxis to contain SARS-CoV-2 in the human body. Most of these studies reported non-significant associations between HCQ prophylaxis and reduced SARS-CoV-2 infection rate,15 19 21 33–50 while only a few reported HCQ prophylaxis could significantly decrease SARS-CoV-2 infection rate 51–59. Our findings of significant association between PrEP use of HCQ and reduced risk of SARS-CoV-2 infection in clinical trials are consistent with another meta-analysis of cohort studies among high-risk HCWs performed by Stricker and Fesler 60.…”
Section: Discussionsupporting
confidence: 87%
“…Since HCQ has proven to be able to prevent SARS-CoV-2 infection in vitro,31 32 a number of clinical trials and observational studies embarked on evaluating HCQ as prophylaxis to contain SARS-CoV-2 in the human body. Most of these studies reported non-significant associations between HCQ prophylaxis and reduced SARS-CoV-2 infection rate,15 19 21 33–50 while only a few reported HCQ prophylaxis could significantly decrease SARS-CoV-2 infection rate 51–59. Our findings of significant association between PrEP use of HCQ and reduced risk of SARS-CoV-2 infection in clinical trials are consistent with another meta-analysis of cohort studies among high-risk HCWs performed by Stricker and Fesler 60.…”
Section: Discussionsupporting
confidence: 87%